Sexuality, gender, media. Identity articulations in the contemporary media landscape. Issue 8 (11th June 2021) - Scarcelli, Cosimo Marco; Krijnen, Tonny; Nixon, Paul
ABSTRACT: From the Trump administration's attempts to narrow down the definition of gender to biologically determined sex at birth to the everyday life gendered performances in digital platforms, from increasing representations of LGBTQI+ in TV programmes to the popularity of PornHub, the relations between gender, sexuality and media are ubiquitous and deeply embedded in everyday life. This Special Issue of Information, Communication and Society draws together cutting-edge contributions on the themes of Gender and Sexuality and Media. Showcasing the work of experienced and internationally renowned scholars and some less experienced but no less relevant voices of emerging scholars. The research upon which the contributions are based analyse media both in terms of representation and agency exploring media texts and the practices of media production and consumption. The special issue provides an accessible and enjoyable, discussion of many of the major themes pertinent to differing uses of digital and other media related to the field of Gender and Sexuality. Investigating nuances of contemporary sex and gender scripts as they are played out in popular media and challenging the heteronormative and sexist performances often encountered. It offers insights upon both 'traditional' and digital media and in some cases illustrates how those two have morphed making it sometimes difficult to clearly define boundaries between the traditional and the digital.